Persuasive Apps for Sustainable Waste Management: A Comparative Systematic Evaluation of Behavior Change Strategies and State-of-the-Art - Nkwo, Makuochi; Suruliraj, Banuchitra; Orji, Rita (Frontiers in Artificial Intelligence, 2021)
With the proliferation of ubiquitous computing and mobile technologies, mobile apps are tailored to support users to perform target behaviors in various domains, including a sustainable future. This article provides a systematic evaluation of mobile apps for sustainable waste management to deconstruct and compare the persuasive strategies employed and their implementations. Specifically, it targeted apps that support various sustainable waste management activities such as personal tracking, recycling, conference management, data collection, food waste management, do-it-yourself (DIY) projects, games, etc. The authors who are persuasive technology researchers retrieved a total of 244 apps from App Store and Google Play, out of which 148 apps were evaluated. Two researchers independently analyzed and coded the apps and a third researcher was involved to resolve any disagreement. They coded the apps based on the persuasive strategies (PSs) of the persuasive system design (PSD) framework. Overall, the findings uncover that out of the 148 sustainable waste management apps evaluated, primary task support (PTS) was the most employed category by 89% (n=131) apps, followed by system credibility support (SCS) implemented by 76% (n=112) apps. The dialogue support (DS) was implemented by 71% (n=105) apps and social support (SS) was the least utilized strategy by 34% (n=51) apps. Specifically, Reduction (n=97), personalization (n=90), real-world feel (n=83), surface credibility (n=83), reminder (n=73) and self-monitoring (n=50) were the most commonly employed persuasive strategies. The findings established that there is a significant association between the number of persuasive strategies employed and the apps’ effectiveness as indicated by user ratings of the apps. How the apps are implemented differs depending on the kind of sustainable waste management activities it was developed for. Based on the findings, this paper offers design implications for personalizing sustainable waste management apps to improve their persuasiveness and effectiveness.